Organizational Mechanism for Environmentally Responsible Education of Youth Considering the Values of Sustainable Development and Security Challenges - Shevchenko, Serhii; Heorhiadi, Nelli; Kucher, Lesia; Fedorchak, Oleksii (European Journal of Sustainable Development, 2025)
The goal of this study is to develop theoretical and applied provisions for the formation of an organizational mechanism for environmentally responsible education of youth, considering the values of sustainable development and security challenges. The study identified the components of the organizational mechanism for environmentally responsible education of youth and clarified the interconnections between them. The environment for forming the organizational mechanism was refined. A system of indicators for monitoring the rationality of the mechanism was developed, and regulatory solutions for its adjustment were proposed. Overall, the authors advanced theoretical and applied provisions for the formation of an organizational mechanism for environmentally responsible education of youth, considering the values of sustainable development and security challenges. Methodological provisions were developed for forming the organizational mechanism for environmentally responsible education of youth, considering the values of sustainable development and security challenges. These provisions are based on a functional-structural scientific approach and, unlike the work of other authors in this area, involve causal parameterization of the organizational mechanism. The proposed methodological provisions for forming the organizational mechanism for environmentally responsible education of youth, considering the values of sustainable development and security challenges, are already being applied in Ukraine within the framework of the project “EcoFortress: Restoring Together.” These methodological provisions can also be implemented in any project activity based on environmental responsibility as a behavioral principle of societal development in the 21st century. Keywords: education, environmental project, environmental responsibility, management, rationality monitoring, security, sustainable development, sustainable education.